How do adults with post‐traumatic stress disorder from childhood trauma talk about single versus repeated traumas?. Issue 4 (25th March 2021) - Memon, Amina; Connolly, Deborah; Brewin, Chris R.; Meyer, Thomas; Seidel, Julia; Anderson, Shelbie; Rijkeboer, Marleen; Arntz, Arnoud
Abstract: Adults with posttraumatic stress disorder from childhood trauma (ch‐PTSD) described their 'worst' traumatic event (a single or repeated event) pre‐post treatment for PTSD during an international clinical trial. The memory reports were coded for specificity ( Episodic vs. General ) and level of detail. Repeated event (RE) narratives contained more generic and fewer episodic references but no more details than memories describing single events (SEs). Analysis of a subset of the sample's post‐treatment memory reports found 38% of the information units were consistent with the pre‐treatment narrative, 38% were omitted, 21% were new details and 2% were changes. The SE and RE groups did not differ on consistency. The data provide a unique insight into single versus repeated event memory reporting in a clinical sample with PTSD from childhood trauma.